Implementasi Standar Operasional Prosedur Sebagai Sistem Informasi Akuntansi Pengeluaran Kas - Istiqomah, Alim Dhisa; Laily, Nujmatul; Santoso, Doni (LPPM Universitas Bina Sarana Informatika, 2023)
Organizational financial management is prone to fraud. The Accounting Information System needs to be implemented by the organization as monitoring. This study aims to determine the application of cash disbursement accounting information system and give recommendations to agencies from the problems. Qualitative case study approach used as a research method. Primary data was collected using observation, interviews, and documentation for five months at the research destination. The results show that accounting information system for cash disbursements at institutions is not strictly regulated. The low regulations make employees less responsible in reporting evidence of cash disbursements transactions. Based on these findings, this study contributes to giving insight for organizations about the importance of implementing system operational procedures as internal control.